Feasibility Study of Housing Project Investment in Batam Center - Sheera Shaviera; Mulia Pamadi; Amanatullah Savitri (Journal of Civil Engineering and Planning (JCEP), 2023)
With population growth, the need for housing as a living space continues to grow in both urban and rural areas. An individual's housing needs vary according to personal and financial circumstances. Before starting construction, a feasibility study should be conducted. The purpose of the analysis is to positively and negatively assess the feasibility of the project in all aspects such as customer satisfaction, expectations and requirement assessment. The analysis is carried out after collecting data, such as plan drawings, budget, and cash flow plans. The feasibility analysis in this report is seen from the technical and financial aspects. In the aspect of technical feasibility seen from the value of KDB and KLB. In terms of financial feasibility seen from the NPV, IRR, PI, and PP value. The KDB value is 42.43% < 60% and the KLB value is 60% £ 60%, with a positive NPV of IDR 31,221,998,389.25, an IRR of 22.41% where the NPV value is zero, PP 2 years < 5 years investment period, and PI 1.22 > 1, it can be said that this project is feasible in technical and financial aspects.